ACUTE TESTICULAR ISCHEMIA CAUSED BY INGUINAL HERNIATION WITH INCARCERATED LOOP OF SIGMOID COLON IN NEWBORN - А. Федорук; А. Писаренко; І. Ревенко (Bukovynian State Medical University, 2024)
The authors report a clinical case of a 14-day-old newborn with a left inguinal hernia with incarceration of the sigmoid loop associated with testicular ischemia, a clinical situation that posed some problems of diff erential diagnosis. The mother of the child was referred to the emergency department. Objective examination revealed hyperemia and edema of the left hemiscrotum, and on palpation there was a hard, irreducible, painful swelling. The child was urgently taken to surgery. On re-examination an incarcerated hernia was found with a viable sigmoid loop with moderate edematous changes. The testis showed obvious ischemic changes. With diffi culty, the sigmoid colon was reduced into the abdominal cavity, after observing the restoration of vascularization of the preserved testis. The postoperative result was positive and the child was discharged in satisfactory condition.